A Review of Ethical Leadership and Other Ethics- Related Leadership Theories - Ahmad, Israr; Gao, Yongqiang; Hali, Shafei Moiz (European Scientific Journal, ESJ, 2017)
The role of ethics in leadership studies is very important for organizations. Leadership without ethics and integrity can be harmful both for the organizational stakeholders and society. The high-profiled scandals and the leadership involvement in unethical activities caused increase attention of the scholars and mainstream media in the leadership ethics (Hartog, 2015). This resulted a growing research in the field of ethical leadership behavior. For this reason, the present study review ethics-related leadership including ethical leadership and other ethic-related leadership theories to better understand the importance of the ethics and morality in these leadership constructs. This study also presented a comprehensive review on ethical leadership and its similarities and differences with other related leadership styles. Another focus of this study was to present the definitions of each leadership style and their scales, and to establish that how ethical leadership is distinct from each leadership style. Future directions and conclusion are presented in the last of the paper.